Pengaruh Harapan Lama Sekolah dan Tingkat Pengangguran terhadap Tingkat Partisipasi Angkatan Kerja di Provinsi Aceh - Zahwa Fazadita; M Afdal Samsuddin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This research aims to examine how the predicted years in school and the unemployment rate influence labor force participation (TPAK) in Aceh Province. Across several cities and communities in Aceh, it employs secondary panel data from the Central Bureau of Statistics (BPS). Panel regression analysis is done using the Random Effect Model (REM) approach in this study. The results show that TPAK is negatively and substantially affected by the unemployment rate, while the projected years of schooling have no significant statistical impact. TPAK changes are generally only marginally affected by either of these causes. The coefficient of determination reveals that the model explains only 8. 3% of the TPAK swings. Although education and unemployment are components of labor market behavior, other, more important variables are more crucial in influencing labor force participation in Aceh, as these results suggest.